Comparison Between the Effects of Continuous and Intermittent Light-Intensity Aerobic Dance Exercise on Mood and Executive Functions in Older Adults - Hyodo, Kazuki; Suwabe, Kazuya; Yamaguchi, Daisuke; Soya, Hideaki; Arao, Takashi (Frontiers in Aging Neuroscience, 2021)
There is a growing body of evidence suggesting that moderately intense acute exercise enhances executive function in older adults. However, in terms of safety, feasibility, and continuity, older individuals prefer light, easy, and fun exercises to moderate and stressful exercises for improving executive function. Therefore, light-intensity aerobic dance exercise (LADE) is suitable if it produces potential benefits related to executive function. As for continuous versus intermittent exercise, intermittent exercise has received a lot of attention, as it results in greater effects on executive function than continuous exercise; however, its effects in older adults remain uncertain. Thus, in this study, we aimed to examine the acute effects of intermittent LADE (I-LADE) in comparison with those of continuous LADE (C-LADE) on mood and executive function. Fifteen healthy older adults participated in 10-min I-LADE and C-LADE sessions on separate days. Perceived enjoyment following exercise was assessed using the Physical Activity Enjoyment Scale (PACES). Pleasantness of the mood during exercise and pleasure and arousal levels after exercise were assessed using the Feeling Scale and Two-Dimensional Mood Scale, respectively. Executive function was assessed using the Stroop task before and after exercise. As a result, pleasantness of the mood during exercise and exercise enjoyment levels were greater in I-LADE than in C-LADE. Arousal and pleasure levels and Stroop task performance increased after both LADEs and did not differ between the two exercise programs. These findings suggest that although enhancement of mood and executive function after exercise did not differ between C-LADE and I-LADE, I-LADE could be more enjoyable and fun than C-LADE. This study will help in the development of exercise programs that enable the elderly to enhance their executive functions in a fun way.